The Filmmaker's Book of the Dead / Draven, Danny : A Mortal’s Guide to Making Horror Movies - Draven, Danny
The book covers every step of the filmmaking process (pre-production, production, post-production, and marketing) and is full of the author's experience and advice. There are also several insightful interviews throughout the book where horror icons such as Stuart Gordon, Robert Englund, and Tom Savini, dispense advice to aspiring filmmakers. The book is beautifully laid out and is full of great images. There is also a companion website to the book where you can download examples of forms used in filmmaking and watch multimedia examples of topics discussed in the book. The Filmmaker's Book of the Dead is an amazing resource for all aspiring filmmakers in any genre.